THE USE OF SOCIOAFFECTIVE STRATEGIES IN AN ONLINE TRANSLATION CLASS. A DIDACTIC PROPOSAL - Mansilla, Diego (2017)
Online translator training has grown considerably in recent years. The virtual classroom modality presents new challenges for instructors, including the need to address the students’ important socio-affective aspects. The socio-affective element in a virtual learning environment directly influences the learning process. This article is based on a socio-constructivist and socio-affective theoretical foundation, a collaborative and contextual pedagogical framework, and a prior survey of recent graduates from an online translation program. We present a didactic proposal focused on the explicit use of socio-affective learning strategies in a virtual translation training program to compensate for the lack of physical presence. The purpose is to improve both the learning process and the translation product. The strategies and tactics proposed are aimed at increasing learner satisfaction, academic results, and the professional preparedness of online translation students.